A common polymorphism rs1800247 in osteocalcin gene was associated with serum osteocalcin levels, bone mineral density, and fracture: the Shanghai Changfeng Study. Issue 2 (February 2016) - Ling, Y.; Gao, X.; Lin, H.; Ma, H.; Pan, B.; Gao, J.
Abstract Summary We evaluated the relationship between a common polymorphism rs1800247 inosteocalcin gene and serum osteocalcin levels, bone mineral density and fracture in Chinese. This was a population-based cross-sectional study. We demonstrated that rs1800247 was associated with bone mineral density and fracture in men and serum osteocalcin levels in women. Introduction This study aimed to evaluate the relationship between a common polymorphism rs1800247 inosteocalcin gene and serum total osteocalcin levels, bone mineral density (BMD) and fracture in Chinese middle-aged and elderly men and women. Methods This was a population-based cross-sectional study included 5561 individuals aged 45 years or older. Information on fractures sustained after age of 45 were collected. BMD at the lumbar spine, femoral neck and total hip were measured using dual-energy X-ray absorptiometry. The genotyping of rs1800247 was performed by matrix-assisted laser desorption/ionization time-of-flight mass spectroscopy. Results rs1800247 was associated with lumbar spine BMD and femoral neck BMD in the dominant model adjusted for age, body mass index (BMI), serum total osteocalcin in men (bothP = 0.04). Besides, rs1800247 was associated with fracture adjusted for age, BMI, serum total osteocalcin and total hip BMD in the additive and dominant models in men (P = 0.04 and 0.01). In the dominant model, the carriers of CC and TC genotypes was associated with a lower odds of fracture compared with the carriers of TT genotype (OR = 0.60, 95%CI 0.40–0.88, P = 0.01). In men, rs1800247 was not associated with serum total osteocalcin levels in additive, dominant or recessive models. However, rs1800247 was associated with serum total osteocalcin levels in all models adjusted for age, BMI, menopausal status and total hip BMD in women (allp < 0.001), with osteocalcin levels decreasing across TT, TC and CC genotypes. rs1800247 was not associated with BMD or fracture in all models in women. Conclusions A common polymorphism rs1800247 inosteocalcin gene may affect the risk of osteoporosis and fracture and serum total osteocalcin levels in Chinese, and there may be gender differences underlying these associations.